Computer Laboratory Inventory Management System of Bestlink College of the Philippines for Senior High School: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The research project titled Computer Laboratory Inventory Management System at Bestlink College of the Philippines was proposed for Bestlink College of the Philippines. The Computer Laboratory Inventory Management System at Bestlink College of the Philippines was made to use staff and admin to manage and monitor the computer. The Computer Laboratory Inventory Management System at Bestlink College of the Philippines is a software-based system that automates the computer laboratory process. It is accessible by the computer laboratory to reduce the possibility of a lost or broken computer. This will help them keep how many computers are in good condition and make it easier to add computer parts. The staff and admin will be notified if the computer to be used is broken. At the planning stage, researchers consider the possible background of the system, looking for a client who is a beneficiary of the system. In the analysis phase, the researchers analyze the client’s process of retrieving computer data. In the design stage, the researcher and the client have a conversation t in a convenient process that has been made. In the development stage, the real work of the conversion process is done. In the testing phase, the researchers did something to debug the system before deploying it. The researcher deployed the system and implemented it at Bestlink College of the Philippines, signing the contract and implementing it on their devices. The maintenance phase follows if the client finds anomalies. The client must contact the programmer for maintenance service.